Understanding of the Rule of Law in the Antipodes - Siekiera, Joanna (International Studies. Interdisciplinary Political and Cultural Journal, 2022)
Understanding the rule of law in the Antipodes, that is in the Commonwealth of Australia and New Zealand, as a legal value is clear to both of these societies. The rule of law, oftentimes called the state of law, is the basis of the system of values, as well as legal culture, which determines which social values are legally protected and how high their position de facto and de iure is. The hierarchy of the rule of law in the Antipodes shows undoubtedly how various legal norms, unwritten and those codified ones, protect the democratic system with all its principles, along with the rights and freedoms of citizens and persons residing in these two countries.